First photographic evidence of the iconic big mammals of Honduras, Baird’s Tapir (Tapirus bairdii) and Jaguar (Panthera onca), in La Muralla Wildlife Refuge - Sagastume-Espinoza, Kevin Omar; Romero, Saulo J. (THERYA, 2017)
In Honduras, the biggest land mammals found are the Baird’s tapir and the jaguar. Both species have been documented previously for La Muralla Wildlife Refuge, Olancho, Honduras, but there has never been photographic evidence of their presence. In the present, we show the first photographic evidence for both species captured using camera-traps during a one month period. With this evidence new conservation efforts can be planned taking in consideration the recent presence of both iconic species in the refuge and the country as well as an important connectivity spot for the species populations.